Subject ordered pointing task performance following severe traumatic brain injury in adults. - Hanten G; Stallings-Roberson G; Song JX; Bradshaw M; Levin HS (Brain Injury, 2003)
The utility of a non-verbal, untimed subject ordered pointing task for identifying memory deficit in adult patients with TBI was tested. Using a cross-sectional design, the working memory performance of 70 adults with severe traumatic brain injury (TBI) and 45 uninjured adults was investigated on a computerized, self-paced, non-verbal subject ordered pointing task. Persons with severe TBI were impaired on measures of working memory relative to the control subjects. In addition, the task appeared to be sensitive to severity of injury as measured by the Glasgow Coma Scale, even within a truncated range of severity (GCS scores 3-8). It was concluded that the subject ordered pointing task is useful in identifying memory deficits in persons with brain injury.